MERIAM PADAM PELITA (TRADISI MENYAMBUT BULAN RAMADHAN DI KERATON KERAJAAN MATAN TANJUNGPURA KABUPATEN KETAPANG) - Sastia, Elsi; Fretisari, Imma; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractSastia, Elsi. 2019. Meriam Padam Pelita (Tradition of Welcoming the Month of Ramadan in the Royal Palace of Matan tanjungpura in Ketapang Regency). Thesis. Performing Arts Education Study Program. Department of Language and Arts Education. Faculty of Teacher Training and Education. Pontianak Tanjungpura University. Advisor I Ismunandar, S.H., S.Sn., M.Pd., And Advisor II Asfar Munir, M.Pd. This research is motivated by the writer's interest as a choreographer of the uniqueness of the lamp cannon lamp which is one of the popular historical items in the Royal Palace of Matan Tanjungpura in Ketapang Regency and then elevates it to an arable dance work. The purpose of this study is to re-introduce a unique event from the sound of the cannon that is turned on when welcoming the holy month of Ramadan is in the Royal Palace of Matan Tanjungpura that is able to turn off the lamp in the vicinity of the ketapang area affected by the sound bias from the cannon. The method used is the method of exploration, analysis and evaluation. Research data is the result of observation and interviews. The type of dance set is a dramatic dance type with a pattern of new dance creation, because the writer as a choreographer presents dynamics, conflict, tension, moral values, and others. The framework of the dish is divided into scenes by presenting five acts, namely the daily life of the Ketapang community, the custom of turning on the cannon to go out the lamp and when the coming of the holy month of Ramadan. The theme of this dance work is literary because it takes some of the impression from a series of events. The analysis of dance works starts from ideas / concepts, frameworks, the selection of dancers, the selection of composers and musicians, the operatives used, as well as choosing what instruments are used to support the dance work.Â Keywords: Meram Padam Pelita(Tradition)